Identification of Metabolites that May Reinforce Colonization Resistance Against Infection in an Antibiotic Augmented Gut - Chan, Carol. (2017)
Abstract: Under homeostatic conditions, the commensal microbes of the microbiota protect themselves and their host against enteric pathogens through colonization resistance. Colonization resistance comprises of three key defense mechanisms: microbial release of antimicrobials, crowding out through competition for nutrients and/or through the microbial release of molecules to stimulate the host immune response. When antibiotics are applied to the microbiota there is a decrease in microbial diversity, weakening the colonization resistance and leaving the host susceptible to pathogenic invasion, infection, and disease. To assess the host and microbial activity under antibiotic stress, preliminary metabolic profiles of differently antibiotic-conditioned mice were generated using untargeted LC-MS/MS detection and a novel annotation pipeline. Analysis of the metabolic profiles identified several metabolites that may reinforce colonization resistance to deter pathogenic establishment in the gut during an antibiotic-stressed state.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Kyongbum Lee.; Committee: Soha Hassoun, and Emmanuel Tzanakakis.; Keywords: Biology, and Microbiology.